Mastering skills for the TOEFL IBT : - Yancey, Patrick (Trẻ, 2006)
In this third and final book of the series, students pratice the innovative question types found on the TOEFL iBT at the level of difficulty seen on the actual test. As with the other books in the series, suggested tips and skill practice exercises are included to help increase scores in all four skill-based test sections: reading, listening, speaking, and writing.